Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(dy=d\left(\dfrac{\sqrt{x}}{a+b}\right)=\left(\dfrac{\sqrt{x}}{a+b}\right)dx=\dfrac{1}{2\left(a+b\right)\sqrt{x}}dx\)
b) \(dy=d\left(x^2+4x+1\right)\left(x^2-\sqrt{x}\right)=\left[\left(2x+4\right)\left(x^2-\sqrt{x}\right)+\left(x^2+4x+1\right)\left(2x-\dfrac{1}{2\sqrt{x}}\right)\right]dx\)
a) = = .
b) = = .
c) = = .
d) y' =\(\dfrac{\left(x^2+7x+3\right)'\left(x^2-3x\right)-\left(x^2+7x+3\right)\left(x^2-3x\right)'}{\left(x^2-3x\right)^2}\)=\(\dfrac{\left(2x+7\right)\left(x^2-3x\right)-\left(x^2+7x+3\right)\left(2x-3\right)}{\left(x^2-3x\right)^2}\)=\(\dfrac{-2x^2-6x+9}{\left(x^2-3x\right)^2}\)
Tham khảo: